A Forgotten Sport: Pedestrianism in the West Midlands. (4th May 2021) - Martin, Derek
ABSTRACT: The modern sport of athletics emphasizes its 'Olympian' ideals and its origins in the public schools, universities and amateur clubs of the late Victorian era. Ironically for a sport that has so successfully commercialized itself and boasts many highly paid professionals, its debt to its predecessor, pedestrianism, the name for running for money, has been relatively neglected. Pedestrianism was a major sporting interest and an abiding part of popular culture in the nineteenth century. This paper, using the example of the West Midlands, traces how the sport adapted itself to urbanization and the leisure industry, encompassed disciplines as varied as sprints and walks of a thousand miles, how it was involved in the growth of the specialist sporting press, pioneered sports arenas and, not least, provided opportunities for female athletes.